ANALYSIS OF TEACHING AND LEARNING ACTIVITIES TO DETERMINE THE QUALITY OF STUDENT LEARNING USING THE K-MEANS CLUSTERING METHOD(CASE STUDY OF SMK MAARIF AL-MIZAN) - Muhammad Abdul Jabbar; Fikri Emsa Silmi; Ahmad Teguh Satria (Politeknik Mardira Indonesia, 2024)
In the world of education there are often problems how to determine the quality in an educational institution and often institutions ignore it, therefore to find out the quality of education in an institution requires clustering using the K-Means method which will be divided into 3 (three) cluster levels, namely